Efficient Synthesis of 3‐Mercaptoindoles via HI‐Promoted Sulfenylation of Indoles with Sodium Sulfinates. Issue 3 (27th March 2023) - Sun, Shengnan; Ye, Hexia; Liu, Haibo; Guo, Yongbiao; Gao, Zhenhua; Pan, Li; Li, Junchen; Bi, Xiaojing
Abstract: A new direct sulfenylation method of indoles by sodium sulfinates and hydroiodic acid was developed giving variety of 3‐sulfenylindoles in high yields under mild conditions without using any catalysts or other additives. In situ‐generated RS‐I species are supposed to be mainly responsible for the key electrophilic alkyl‐ or aryl‐thiolation process. Abstract : A new direct sulfenylation method of indoles by sodium sulfinates and hydroiodic acid was developed giving variety of 3‐sulfenylindoles in high yields under mild conditions without using any catalysts or other additives. RS‐I species generated in situ are supposed to be mainly responsible for the key electrophilic alkyl‐ or aryl‐thiolation process.